Restoration and highlight of Agioi Theodoroi church in Nafplio with the use of CAD technologies - Psychogyios, Dimitris; Leptidou, Katerina (Technical Annals, 2023)
The church of Agioi Theodoroi is located north of the new city of Nafplion, in the “Neo Byzantio” or “Kültepe” area, near the main road connecting Naflion to Argos, on Kalamata Street. It is a small, simple construction, single aisled church with pitched tiled roof and a semi-circular sanctuary arch. The church is not pro-claimed monument, but it constitutes important historical evidence of recent history of the city and of Greece in general, given that it is documented to be associated with one of the protagonists of the Revolution of 1821 Theodoros Kolokotronis and therefore it is inextricably linked to the collective historical memory. Today the church belongs to “Holy Church of Saint Constantine and Helen” in Naflion. Due to celebrations for the 200 years anniversary of the Greek revolution, the committee “Greece 2021” has approved the financing of its restoration. This paper presents the initial diagnostic procedures as well as the first results from the plaster removals and the test sections in the construction field. The diagnostic procedures include the creation of multidisciplinary thematic maps in Computer Aided Design (CAD) environment, which incorporate: (a) data of historical and architectural documentation (b) data of geometric documentation and (c) data of building materials characterization and decay diagnosis. It is about a work in progress and is proceeding with multidisciplinary collaboration between historians, architects, archeologists, material science engineers. Of particular interest is the involvement of the local community in support of the project and in archival/bibliographic research. Finally, the completion of the project will bring changes to the map of the city’s points of historical interest since it is located outside the historic city center. This event should have as its goal both the sustainable protection of the monument as well as the sustainable development of the wider area